Micro-blog and the speech act of China's middle class - Changchang, Wu (Javnost (Ljubljana), 2012)
This article explores the impetus, processes, as well as discursive dispositions through which members of the Chinese middle class mounted a challenge against the state-owned railway system and the entire Chinese political structure in the blogsphere in the aftermath of a devastating train accident on July 23, 2011. The analysis underscored the pivotal "organic intellectual" role of journalists, lawyers, and public intellectuals in helping to construct the "class consciousness" and subjectivity of an anxious,ambivalent and insecure networked middle class in China's rapidly polarising social formation. However, not only this "stand out" collective action of the Chinese middle class was the result of many contingencies but also the apparent uniformity of their speech acts concealed deep fissures. Moreover, the naive liberalism and anti-statist sloganeering that underpins the dominant micro-blog discourse eventually displaced and blocked any possibility for discussing and advancing the concrete processes of reforming China's state-owned system and democratising Chinese politics.
Keywords: Kitajska; družbene razmere; politične razmere; politična elita; mass media; množični mediji; informiranje; svetovni splet; komuniciranje; communication; internet (računalniško omrežje); vplivi; javnost; javno mnenje; democracy; demokracija